Effectiveness of fenugreek as a galactagogue: A network meta-analysis - Khan, T.; Wu, D.; Dolzhenko, Anton (John Wiley and Sons Ltd, 2018)
Copyright © 2017 John Wiley & Sons, Ltd. A systematic review and network-meta analysis (NMA) were performed to test significance of the galactagogue effect of fenugreek administrated to lactating women versus other comparators (i.e., placebo/control/other galactagogues). A pairwise comparison for the treatment effect was carried out to generate the forest plot for the NMA. League tables were generated using treatment effect, weighted mean difference (WMD; 95% confidence interval, CI) for all pairwise comparisons, where WMD  >  0 favors the column-defining treatment. Five studies were identified with 122 participants receiving treatment with fenugreek. The NMA results of 4 studies indicated that consumption of fenugreek significantly increased amount of the produced breast milk [11.11, CI 95% 6.77, 15.46] versus placebo. The pairwise comparison revealed that fenugreek was effective as a galactagogue compared to placebo, control, and reference groups WMD 17.79 [CI 11.71, 23.88] . However, the effect of fenugreek was substantially inferior to Coleus amboinicus Lour and palm date. The NMA using pairwise comparison demonstrated the effect of C. amboinicus and palm date in the stimulation of the breast milk production was comparable and superior to all comparators.